Allenylidene complexes based on pentacenequinone - Strinitz, Frank; Waterloo, Andreas; Tucher, Johannes; Huebner, Eike; Tykwinski, Rik; Burzlaff, Nicolai (European Journal of Inorganic Chemistry, 2013)
Stable ruthenium-allenylidene complexes based on pentacenequinone have been synthesized. The complexes show an electronic absorption in the NIR region that arises from forbidden MLCT transitions, as explained by DFT calculations. The crystal structure reveals promising features for the formation of metal-influenced organic FETs. Stable ruthenium-allenylidene complexes based on pentacenequinone have been synthesized. The depicted complex shows an electronic absorption in the NIR region that arises from forbidden MLCT transitions, as explained by DFT calculations. The crystal structure reveals promising features for the formation of metal-influenced organic FETs. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Carbon-rich cyclopentadienyl ruthenium allenylidene complexes - Spörler, Susanne; Strinitz, Frank; Rodehutskors, Philipp Maximilian; Müller, Lisa; Waterloo, Andreas; Dürr, Maximilian; Hübner, Eike; Ivanovic-Burmazovic, Ivana; Tykwinski, Rik; Burzlaff, Nicolai (New Journal of Chemistry, 2016)
Ruthenium allenylidene complexes with carbon-rich polyaromatic moieties have been synthesized by using [RuCl(η-CH)(PPh)] (η-CH = cyclopentadienyl) as a precursor and the propargyl alcohols 10-ethynyl-10-hydroxyanthracen-9-one (ACO), 13-ethynyl-13-hydroxypentacen-6-one (PCO), 1-phenyl-1-(pyren-1-yl)prop-2-yn-1-ol (PyrPh), 9-ethynyl-9H-fluoren-9-ol (FN) and 6-ethynyl-6H-benzo[cd]pyren-6-ol (BPyr) as ligands. The resulting cationic allenylidene complexes, [Ru(η-CH)(CC(AO))(PPh)]PF (1), [Ru(η-CH)(CC(PCO))(PPh)]PF (2), [Ru(η-CH)(CC(PyrPh))(PPh)]PF (3), [Ru(η-CH)(CC(FN))(PPh)]PF (4), and [Ru(η-CH)(CC(BPyr))(PPh)]PF (5) show interesting intermolecular π-interactions in the solid-state structure as well as solution state complexation with pyrene (documented by Job's plots experiments). CV data indicate possible Ru(ii)/Ru(iii) oxidation, as well as the potential reduction of the carbon-rich allenylidene moiety.

Ruthenium carbonyl complexes bearing bis(pyrazol-1-yl)carboxylato ligands - Türkoglu, Gazi; Tampier, Stefan; Strinitz, Frank; Heinemann, Frank Wilhelm; Huebner, Eike; Burzlaff, Nicolai (Organometallics, 2012)
The syntheses of the two dicarbonyl complexes [Ru(bdmpza)Cl(CO) ] (3) and [Ru(2,2-bdmpzp)Cl(CO) ] (4), bearing a bis(3,5-dimethylpyrazol-1-yl)acetato (bdmpza) or a 2,2-bis(3,5-dimethylpyrazol- 1-yl)propionato (2,2-bdmpzp) scorpionate ligand, are described. Both complexes are obtained by reacting the polymer [RuCl (CO) ] with either K[bdmpza] or K[2,2-bdmpzp]. Reaction of the acid Hbdmpza with [Ru (CO) ] results in the formation of two structural isomers of a hydrido complex, [Ru(bdmpza)H(CO) ] (5a,b). Under aerobic conditions conversion of [Ru(bdmpza)H(CO) ] (5a,b) to form the Ru(I) dimer [Ru(bdmpza)(CO)(μ-CO)] (6) seems to be hindered in comparison to the case for the η -C H (Cp) analogues. Dimer 6 is obtained via a reaction of Hbdmpza with catena-[Ru(OAc)(CO) ] instead. The molecular structures of 3, 4, and 6 have been obtained by single-crystal X-ray structure determinations. The precatalytic properties of the two dicarbonyl complexes 3 and 4 toward the catalytic oxidation of cyclohexene with different oxidizing agents are discussed as well. © 2012 American Chemical Society.